RELEVANSI PEMIKIRAN K.H.A.WAHID HASYIM DENGAN PENDIDIKAN AGAMA ISLAM DI ERA KONTEMPORER - Abdi Ardiansyah Sihotang; Nurmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relevance of K.H. A. Wahid Hasyim's thoughts in relation to the development of Islamic Religious Education (PAI) in the contemporary era. As a prominent Islamic reformer and the first Minister of Religious Affairs of the Republic of Indonesia, K.H. Wahid Hasyim is known for his progressive ideas that integrate Islamic values with nationalism and modernity. This research employs a qualitative approach using library research methods, analyzing his ideas through works, speeches, and relevant historical documents. The findings indicate that his thoughts are highly relevant to the current needs of Islamic education, particularly in shaping moderate, tolerant, and open-minded individuals in the face of scientific and technological progress. His educational philosophy emphasizes moral values, national character development, and adaptability to social change. Therefore, integrating the values of K.H. Wahid Hasyim’s thought into the Islamic education curriculum and practices is crucial in addressing the challenges of globalization and radicalism.